MENGEMBANGKAN MADRASAH ALIYAH NEGERI INSAN CENDIKIA UNTUK MENJAWAB TANTANGAN MODERNISASI, DEMOKRATISASI DAN GLOBALISASI (DEVELOPING INSAN CENDIKIA HIGH SCHOOL TO ADDRESS MODERNISATION, DEMOCRACY, AND GLOBALISATION CHALLENGES) - Makmuri Sukarno (Research Centre for Population, Indonesian Institute of Sciences, 2014)
Madrasah Aliyah Negeri Insan Cendekia (MAN-IC) faces, similar with other schools, disfunctional in preparing people that are more qualified, if the institution does not reform it-self along with the strategic challanges which are developing. MAN-IC, that was build based on Modernist-Islam spirit, is a model madrasah especially with regard to its religious and science & technology teaching practices. Nowadays, this institution is not only challanged with old challanges, that are searching Islamic as well as Indonesian characters and modernization, but also with the new ones, that are democratization including local otonomy and globalization. Rapid Assessment method to see its governance, management, curriculum, and teaching-learning aspects within the two of three existing MAN-ICs (which are located in Jakarta and Jambi) reveals the imbalances and unreadiness of those institution in facing those challanges. Reform on those aspects proposed by this article is assumed to be empowering its responsive ability in preparing future